Receptors for advanced glycation end-products targeting protect against hyperoxia-induced lung injury in mice - Reynolds, Paul; Schmitt, Robert E.; Kasteler, Stephen D.; Sturrock, Anne; Sanders, Karl; Bierhaus, Angelika; Nawroth, Peter Paul; Paine, Robert; Hoidal, John R. (American journal of respiratory cell and molecular biology, 2010)
Patients with acute lung injury almost always require supplemental oxygen during treatment; however, elevated oxygen itself is toxic. Receptors for advanced glycation end-products (RAGE) are multiligand cell surface receptors predominantly localized to alveolar type I cells that influence development and cigarette smoke-induced inflammation, but studies that address the role of RAGE in acute lung injury are insufficient. In the present investigation, we test the hypothesis that RAGE signaling functions in hyperoxia-induced inflammation. RAGE-null mice exposed to hyperoxia survived 3 days longer than age-matched wild-type mice. After 4 days in hyperoxia, RAGE-null mice had less total cell infiltration into the airway, decreased total protein leak, diminished alveolar damage in hematoxylin and eosin-stained lung sections, and a lower lung wet-to-dry weight ratio. An inflammatory cytokine antibody array revealed decreased secretion of several proinflammatory molecules in lavage fluid obtained from RAGE knockout mice when compared with wild-type control animals. Real-time RT-PCR and immunoblotting revealed that hyperoxia induced RAGE expression in primary alveolar epithelial cells, and immunohistochemistry identified increased RAGE expression in the lungs of mice after exposure to hyperoxia. These data reveal that RAGE targeting leads to a diminished hyperoxia-induced pulmonary inflammatory response. Further research into the role of RAGE signaling in the lung should identify novel targets likely to be important in the therapeutic alleviation of lung injury and associated persistent inflammation.
Zuerst veröffentlicht am 25. Juni 2009
Gesehen am 15.05.2023